2018
DOI: 10.25115/ejrep.v16i46.2236
|View full text |Cite
|
Sign up to set email alerts
|

Procrastination and Learned-Helplessness among University Students: The Mediation Effect of Internal Locus of Control

Abstract: Introduction. Previous studies indicated that more than 70% university students committed academic procrastination, and one of the most prominent factors is learned helplessness, the perception that one is incapable of finishing tasks well. It was also hypothesized that when students believe that they are in control of their own events, their learned helplessness will not significantly predict their academic procrastination. This current study aims to test the hypothesis whether internal locus of control media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Findings of this study enrich the previous studies in the similar context of Malaysian educational settings. When Prihadi et al [13] reported the mediation role of ILOC on the link between learned helplessness and academic procrastination, there was still a question whether ILOC is a major significant factor that decrease academic procrastination, up to an extent where it can alter the influence of learned helplessness. This current study indicates that ILOC, despite its significant prediction, is also mediated by classroom engagement; in other words, students with high internal locus of control still need to be engaged in their classroom environment in order to reduce their procrastination behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings of this study enrich the previous studies in the similar context of Malaysian educational settings. When Prihadi et al [13] reported the mediation role of ILOC on the link between learned helplessness and academic procrastination, there was still a question whether ILOC is a major significant factor that decrease academic procrastination, up to an extent where it can alter the influence of learned helplessness. This current study indicates that ILOC, despite its significant prediction, is also mediated by classroom engagement; in other words, students with high internal locus of control still need to be engaged in their classroom environment in order to reduce their procrastination behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth to note that self-esteem was also reported as a strong predictor of procrastination [8]. In line with that, another study in Malaysian context reported that when students believe that they are in control of their events (possess high level of internal locus of control), the less likely they will procrastinate doing their tasks although they believe that they are incapable of finishing the task properly [13]. Other than that, external factors such as the existence of a well-structured academic goal predicts the decrease of academic procrastination [2] and a recent study done in a mathematics class (8 th and 10 th grade students) showed that intrinsic motivation and effort are predicted by goal structures that aim to promote autonomy and personal achievement [18]; whereby students tend to cope better with their academic related tasks when they set goals [19].…”
Section:  Issn: 2252-8822mentioning
confidence: 89%
See 2 more Smart Citations
“…This could be conveying students’ accommodation skills to deal with a negative outcome, such as when students are easily accepting of a poor grade but are able to reflect on how they can learn or benefit from the outcome. This may be valuable given the toxic role of helplessness in achievement settings that can lead to academic procrastination and lower performance in domain-specific courses (Krejtz & Nezlek, 2016 ; Prihadi et al, 2018 ), but also given the pressures and unpredictability experienced by emerging adults during this critical time point in development (Arnett, 2000 ). These findings may also point to the relevance of targeting or promoting these SC beliefs for individuals who may be susceptible to helplessness.…”
Section: Discussionmentioning
confidence: 99%